Combined correction of the nasal tip and upper lip in bilateral cleft lip patients: A novel approach. (November 2019) - Ujam, Atheer B.; Vig, Navin; Nasser, Nasser
Abstract: Secondary nasal deformity in bilateral cleft lip is one of the great surgical challenges. The problems are an under projected tip, an infra-tip lobule merging with the pro-labium and a short columella. Upper lip vermillion border deformity is a further significant problem. We demonstrate our novel approach to management by classifying patients into 3 groups depending on the status of important features such as the anatomy of the prolabial skin island, length of columella and upper lip width and fullness. We demonstrate that cleft patients with nasal deformity and poor upper lip aesthetics can be managed with a single operation.